Efektifitas Peer Teaching Model Dalam Kurikulum Merdeka Terhadap Kemampuan Teknik Dasar Passing Dalam Pembelajaran Bola Basket Pada Siswa dan Siswi Kelas 7 SMP Negeri 3 Klari - Baihaqi Akbar; Ega Trisna Rahayu (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research was conducted to determine the effect of the drill method on the basketball passing skills of grade 7 students at SMP Negeri 3 Klari. This research is an experimental research to find out whether the drill method can affect basic passing skills in teaching basketball for grade 7 at SMP Negeri 3 Klari. The number of samples is 28 students taken by purposive sampling technique where the sample criteria is based on the class that is willing to be given the drill method. The research data was carried out with one group pretest-posttest design. Results obtained through normal-ity data test with the results stating that the pretest data was 0.021 > 0.05 and the posttest was 0.085 > 0.05. the pretest-posttest results stated that the data were distributed homogeneously and the t-test calculation obtained the Sig value. (two cultivated) 0.000 < 0.05 means a significant difference in the results before and after treatment. it can be concluded from the results of research conducted can be stated that there is an influence of the drill method on the ability to pass basketball at SMP Negeri 3 Klari.